Host-pathogen interactions of clinical S. aureus isolates to induce infective endocarditis. Issue 1 (31st December 2021) - Schwarz, Christian; Töre, Yasemin; Hoesker, Vanessa; Ameling, Sabine; Grün, Katja; Völker, Uwe; Schulze, P. Christian; Franz, Marcus; Faber, Cornelius; Schaumburg, Frieder; Niemann, Silke; Hoerr, Verena
ABSTRACT: To evaluate potential pathomechanisms in the induction of infective endocarditis (IE), 34 Staphylococcus aureus ( S. aureus ) isolates, collected from patients with S. aureus endocarditis and from healthy individuals were investigated both in vitro and in vivo. S. aureus isolates were tested in vitro for their cytotoxicity, invasion and the association with platelets. Virulence factor expression profiles and cellular response were additionally investigated and tested for correlation with the ability of S. aureus to induce vegetations on the aortic valves in vivo . In an animal model of IE valvular conspicuity was assessed by in vivo magnetic resonance imaging at 9.4 T, histology and enrichment gene expression analysis. All S. aureus isolates tested in vivo caused a reliable infection and inflammation of the aortic valves, but could not be differentiated and categorized according to the measured in vitro virulence profiles and cytotoxicity. Results from in vitro assays did not correlate with the severity of IE. However, the isolates differed substantially in the activation and inhibition of pathways connected to the extracellular matrix and inflammatory response. Thus, comprehensive approaches of host-pathogen interactions and corresponding immune pathways are needed for the evaluation of the pathogenic capacity of bacteria. An improved understanding of the interaction between virulence factors and immune response in S. aureus infective endocarditis would offer novel possibilities for the development of therapeutic strategies and specific diagnostic imaging markers.